Pemberdayaan Masyarakat dalam Pengolahan Sampah untuk Mendukung Insrastruktur yang mendukung Pariwisata dan Ekonomi Kreatif Masyarakat di desa Tuapajet Kabupaten Mentawai - Lolom Evalita Hutabarat (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
This community service project is part of an ongoing campaign in the Mentawai Islands to prepare for a healthy, environmentally friendly tourism resort following the Covid-19 endemic. Four large and tiny islands make up the Mentawais (252 units). Siberut, Sipora, and North and South Pagai are large islands. The sub-district capital of the Mentawai Islands Regency is 2 meters above sea level (DPL). Mentawai Islands Regency's capital is Tuapejat, 153 km from Padang. Only water can access West Sumatra's wealth. FGD programs are a village service. As a contribution to the Civil Engineering Study Program FT UKI, which focuses on a sustainable environment, by focusing on community empowerment in waste management to prepare infrastructure that supports Tourism and the Creative Economy of the village. Garbage piles pollute Mentawai Regency Tuapajet Environmental. Several campaigns aim to raise environmental awareness. As government partners in the FT UKI Civil Engineering Study Program, universities must help reach coastal communities like the Mentawai Islands. Residents underestimate the impact of a considerable volume of waste piled up in residential areas due to a lack of education. Since 2006, the government has used television to promote 3R household garbage management (Reduce, Reuse, Recycle). Various campaign strategies apply the 3R principles to raise public awareness of waste management.